A new species of Gordius (Nematomorpha, Gordiidae) from the karstic caves in the Wuling Mountains, Central China - Ya-Zhen Zou; Jie Huang; Hai-Yang Xiang; Shi Li; Yan Tang; Zhi-Xiao Liu (Zoosystematics and Evolution)
Gordius wulingensis sp. nov., a newly described horsehair worm, parasitizes Tachycines (Orthoptera, Rhaphidophoridae). Free-living specimens are mainly found in karstic cave puddles. In recent years, a total of 37 creamy white horsehair worms were collected from various caves in the Wuling Mountains. Characteristic for the species is that males exhibit concentrated bristles at the tips of the inner lobes and scattered bristles along the posterior half of the caudal lobe. The inner wall of the cloacal opening displays honeycombed areoles. The body cuticle contains dense bristles in the anterior and posterior ends; the density of bristles is decreasing in the mid-body. Distinct longitudinal sharp ridges are visible on the ventral and dorsal surfaces. Adults are present in caves year-round, while the entire life cycle is completed within the caves. In the laboratory, specimens can be kept alive for more than 3 months.